Programming PHP - Lerdorf, Rasmus (O'Reilly, 2006)
Introduction to PHP; Language Basics; Functions; Strings; Arrays; Objects; Web Techniques; Databases; Graphics; PDF; XML; Security; Application Techniques; Extending PHP; PHP on Windows.